Development of behavioural regulation in Do and Don't contexts among behaviourally inhibited Chinese children. (1st March 2016) - He, Jie; Zhai, Shuyi; Lou, Liyue; Zhang, Qing; Li, Zhuyun; Shen, Mowei
Abstract : Behavioural inhibition influences the development of behavioural regulation in early childhood. Previous studies have mainly focused on the relationship between inhibition and regulation in the Don't context (e.g., inhibitory control), while few have investigated this relationship in the Do context (e.g., task persistence). This longitudinal study examined the effect of temperamental inhibition on behavioural regulation during both the Do and Don't contexts in 112 Chinese preschoolers. At 3.5 years of age, children's behavioural inhibition was assessed by behavioural observation and parental report, and then at 4.5 years of age, their regulatory behaviours were measured in the following two challenging contexts: Do [locked box (LB)] and Don't [toy inhibition (TI)]. In each task, children were randomly assigned to either a high‐ or a low‐incentive condition designed to vary the value of a given goal. Results suggested that higher inhibition was associated with poorer regulation (lower task persistence) in both conditions of the Do context (LB), whereas in the Don't context (TI) highly inhibited children showed better regulation (less violation behaviours) in the low‐incentive condition than they did in the high‐incentive condition. The results highlight the context characteristics and goal incentive as important factors for behavioural regulation development in inhibited children in China.